Managing international river basins: reviewing India-Bangladesh transboundary water issues - Sood, Aditya; Mathukumalli, B.K.P. (Informa UK Limited, 2011)
As the demand for fresh water has increased over the years, the conflicts between water-sharing countries have also been on the rise. Many countries, such as Bangladesh in Asia, depend upon water originating from outside their national borders and hence do not have any control in the headwaters and large part of the watershed management of their rivers. Being militarily and economically weaker than its neighbours, it cannot influence their watershed management policies. Consequently, it suffers from both floods and water scarcity. This paper looks at the long-standing conflict between Bangladesh and India with regard to the sharing of water of the River Ganges. It discusses the water quantity and quality problems faced by Bangladesh and its inability to negotiate an equitable deal with India. In order to reduce the water-sharing conflict between Bangladesh and India, a multi-national watershed management approach is required.